QUALITY ASSESSMENT SERVICE OF DAYCARE LIVING IN JAKARTA - Ariani, Meiliyah; Zulhawati (Universitas Teknologi Yogyakarta, 2019)
The young mothers of careers who live in metropolis and as people with toddlers especially in Jakarta Capital Special Region, today faces a variety of challenges; one of which is how to take care of their toddlers. In the face of such phenomenon, emerging business activities that offer service programs to take care of children under five with various facilities along with all its limitations. Whether with the emergence of service businesses to take care of children under five especially in metropolis, already provide quality services for customers so feel safe and comfortable to continue their career? To do research of such phenomenon, selected two subjects residing in Jakarta; that are: ?The Harvest Daycare? and ?Baby Kangaroo?. Is the quality of services provided from both day care is already in